Japanese-as-a-foreign-language acquisition affects native Chinese lexical processing among Chinese learners - Cai, Fengxiang; Fei, Xiaodong; Song, Qichao (Frontiers in Psychology, 2025)
Existing research has primarily focused on the influence of the native language on second language (L2) acquisition and processing, with less attention given to whether L2 acquisition affects native language processing. This study examines Chinese learners of Japanese, focusing on the orthographic and phonological similarities between two-character words in Chinese and Japanese. It investigates how these similarities affect native Chinese lexical processing at intermediate and advanced stages of Japanese learning and explores the predictive effect of L2 lexical processing efficiency on native language lexical processing efficiency at different stages of L2 learning. Through a comparison with native Chinese speakers who have not learned Japanese, the results indicate that L2 Japanese acquisition significantly impacts native Chinese lexical processing for Chinese learners of Japanese. Additionally, although there are some indications of the effects of orthographic and phonological similarities between Chinese and Japanese on native Chinese processing, the overall impact appears to be relatively weak. Moreover, the impact of L2 proficiency on lexical processing is influenced by L2 lexical processing efficiency, with both factors being closely related and jointly affecting lexical processing. Based on these results, this study proposes a potential pathway for native Chinese lexical processing among Chinese learners of Japanese.